INNOVATIVE METHODS FOR ENHANCING THE EFFECTIVENESS OF PRACTICAL GRAMMAR LESSONS IN PHILOLOGY. - Cho’lliyeva Malika Xolmurodovna, (KONFERENSIYALAR, 2025)
Abstract.  University-level  philology  students  often  perceive  traditional grammar  instruction  as  tedious,  prompting  a  need  for  innovative  teaching approaches21 This theoretical article explores how methods such as gamification, blended  learning,  mobile-assisted  learning,  AI-based  grammar  tools,  flipped classrooms, and digital collaboration platforms can reinvigorate practical English grammar  lessons  for  philology  undergraduates.  Grounded  in  constructivist  and communicative  pedagogies,  Bloom’s  taxonomy,  and  principles  of  learner autonomy, we discuss each innovative approach’s conceptual underpinnings and potential  impact.  We  argue  that  these  methods  create  more  engaging,  student-centered learning environments that foster deeper understanding and practical use of grammar, in contrast to traditional rote learning. Personal reflections address the  real-world  practicality,  challenges,  and  effectiveness  of  implementing  these innovations in academic contexts.